Comparative study on pulse distortion and phase aberration of directive ultra-wideband antennas - Tokan, Nurhan Turker; Neto, Andrea; Tokan, Fikret; Cavallo, Daniele (INST ENGINEERING TECHNOLOGY-IET, 2013)
The authors study and compare the properties of two types of highly directive broadband antennas: linear tapered slot antenna (LTSA) and leaky lens antenna (LLA). The performance in terms of dispersion and phase centre stability is investigated for both antennas over a bandwidth exceeding 1:3, by means of experimental results. The pulse distortion is quantified by calculating the angular dependence of the fidelity factor directly from the measurements. The phase centre movement with frequency is also measured and the corresponding phase error loss is estimated when these antennas are to be used as wideband feeds of reflectors. As a consequence of its high phase centre stability, LLA achieves better efficiency than LTSA in terms of phase aberration for broadband reflector systems. However, the efficiency of LTSA can be considerably enhanced by proper positioning of the antenna along the reflector axis.
Keywords: NON DISPERSIVE RADIATION; UWB ANTENNAS; DESIGN; Engineering; Telecommunications